Maqasid-based protection assessment model for user-generated content / Sharifah Aliman - Aliman, Sharifah (2017)
Social media applications allow users to not only generate their own content (user-generated content(UGC)) but also to share with other social media users. Due to the dynamics and real-time publications of social media, many social media users lack the ability to think deeply or to acknowledge the negative impacts of their content that could harm on themselves or others in similar situations. The purpose of this research is to investigate how social media users protect themselves and others whilst using various social media. Literature shows that the disseminated food-based UGC without a filtering phase as this may contain disinformation and misinformation that can lead to such risks as false rumours, deception, panic situations, loss of credibility and a loss of reputation. In contrast to Western humanistic theories, Islamic principles offers an integral spiritual facet on protection measures that may serve as a form of self-awareness and self assessment instrument for social media users and their online activities. Thus, this study proposes a new protection assessment model based on the Maqasid Al-Shariah framework. The model accentuates the essentials (called darurriyat in Arabic) dimensions of Maqasid Al-Shariah, which embraces the protection of faith, life, intellect, property and posterity. The study will design a Maqasid-based protection assessment model (named the MQPA model) that will be used for personal food blogs because blogs are still a prime social media issue in Malaysia. Islamic educators and psychometrics experts have reviewed the proposed MQPA model. The MQPA model instrument has been employed as an online survey tool to gain insights from convenient sample of social media users, i.e. food bloggers. After the data was collected, it underwent the Rasch analysis. The results show that the protection of life, intellect and property are utmost noticeable traits whilst the protection of posterity and faith are the least. Meanwhile, safety brand personality and motivation usage are considered to be contradict in which the safety brand personality is the easiest influential factor on a social media users/ decision about the food products and services under discussion. The protection profiling from the validated MQPA model portrays fresh recognition of the Maqasid-based protection behaviour element of the model. Moreover, this research has proven that the MQPA model is fit to be developed as a web-based visualization application. The MQPA prototype successfully displays the graphical frequency distribution of protection measures based on the Maqasid Al Shariah that vividly visualizes the Shariah friendliness of food-based UGC. The friendliness of the Maqasid-based protection model is an innovative way of self-safeguarding for social media users, especially Muslim users, to assist in thoughtful behaviour whilst dealing with vibrant and instant dissemination.